Tomato Spotted Wilt Virus Benefits Its Thrips Vector by Modulating Metabolic and Plant Defense Pathways in Tomato - Nachappa, Punya; Challacombe, Jean; Margolies, David C.; Nechols, James R.; Whitfield, Anna E.; Rotenberg, Dorith (Frontiers in Plant Science, 2020)
Many plant viruses have been shown to manipulate vector biology and behavior in ways that enhance virus transmission. However, the molecular mechanisms underlying this manipulation are not well-understood. In the current study, we report that infection of tomato plants with a plant virus, tomato spotted wilt virus (TSWV), altered host plant responses in ways that enhanced the likelihood of transmission by its primary insect vector, western flower thrips (Frankliniella occidentalis). Overall, we found that TSWV induced salicylic acid (SA)-responsive genes and suppressed a large proportion of jasmonic acid (JA)-responsive genes that are induced by thrips feeding. This potential antagonistic crosstalk between the SA and JA signaling pathways could benefit feeding thrips. Virus infection suppressed genes associated with photosynthesis and chloroplast function, which may have resulted in the yellow color of virus-infected plants that is thought to be attractive to thrips. Virus infection also suppressed genes related to cell wall organization which may render plants more susceptible to the penetration of thrips mouthparts. Lastly, TSWV infection increased expression of genes related to protein synthesis and degradation which is reflected in the increased total free amino acid content in virus-infected plants that harbored higher thrips populations. These results suggest multiple plant responses through which TSWV manipulates its thrips vector. Findings of this study increases our fundamental knowledge of host plant-virus-vector interactions and identifies important candidate pathways and genes underlining mechanisms of vector manipulation by a plant virus.